Financial times mastering finance : (Wharton, 1998)
FT Mastering Finance brings together the latest in financial expertise from three of the best finance schools in the world. Built around three core modules - corporate finance, investment and financial markets - it provides an understanding and application of financial skills, covering such areas as capital structure, floors, random walk and risk management.